ECONOMIC IMPACT OF COVID-19 ON ROMANIA’S CAPITAL DENTAL PRACTICES - Delia Rădoi; Mihaela Pantea; Marina Imre; Alexandra Ripszky Totan; Ana Maria Cristina Țâncu; Ana Cernega; Miruna-Maria Apetroaei; Silviu Mirel Pițuru (Romanian Journal of Oral Rehabilitation)
This paper examines the economic impact of the COVID-19 pandemic on private dental practices in Bucharest, Romania, focusing on the influence of practice size and employee numbers. A comparative analysis was conducted across three years: 2019, 2020, and 2021, utilizing data sourced from the Romanian Finance Ministry. In 2019, there were 1,735 active dental practices, but this number declined to 1,704 in 2020 and further to 1,644 in 2021. Key financial indicators (KFIs) such as turnover, profit, revenue, expenses, debts, and employee numbers were analyzed. The findings revealed a significant decrease in turnover and revenue in 2020 compared to 2019 (p < 0.001), with larger practices (those employing more than three individuals) facing a greater economic burden than smaller ones. However, in 2021, larger practices demonstrated a significant recovery, showing higher increases in turnover, profit, and revenue compared to the smaller ones (p < 0.001). This research shows how important adaptable workforce management is in a dental practice for staying profitable during economic crises. This paper suggests that dental practices should create strategies to improve their resilience against future crises based on these findings.